Evaluation and comparison of African swine fever virus and vaccinia virus cell entry pathways - Olcha, Matthew Evan (Kansas State University, 2020)
African swine fever virus (ASFV) causes a highly contagious and deadly disease in swine, with severe economic consequences. In the absence of a vaccine, control measures that target ASFV replication steps are being actively pursued. Due to the high risk of ASFV and its foreign animal disease status, in the United States it is regulated as a select agent and requires BSL-3 containment. In addition, virulent strains of ASFV require primary cells for propagation in tissue culture. In the face of these limitations the ability to use less restrictive surrogate viruses is attractive. One such option is Vaccinia virus (VV), a member of family Poxviridae. Though VV has been used in this capacity before, investigation into its use in Vero cells are limited. When examined using Vero cells treated with various chemical inhibitors, VV produced similar results as the Vero cell adapted strain of ASFV, suggesting the two viruses behave similar during cell entry and early infection. VV provides a suitable surrogate virus for ASFV research, as well as a virus that can replicate in both Vero cells and primary swine macrophages, though there are limited studies regarding the latter. Swine macrophages and monocytes are the primary target cells for ASFV infection, though factors responsible for this tropism are unknown. A significant body of work identified CD163 as required for ASFV cell entry; however, macrophages lacking CD163 and CD163 knockout pigs support infection. ASFV also utilizes macropinocytosis, a non-specific cellular uptake pathway, to enter the cell. This may explain why CD163KO pigs can be infected with ASFV. The present data indicates that CD163 is not required for ASFV infection, but does not rule out its involvement entirely. Macropinocytosis inhibitors used in all experiments included EIPA, cytochalasin D, and wortmannin. Inhibitors of clathrin-mediated endocytosis included chlorpromazine and dynasore. ML-7 inhibits myosin light chain kinase and nocodazole inhibits microtubule dynamics. All seven inhibitors reduced the infection rate, consistent with ASFV using both macropinocytosis and clathrin- and dynamin-dependent endocytosis, as well as non-muscle myosin II and microtubules during stages of entry and early infection. However, the inhibitor effects were not significantly different between wildtype and CD163KO macrophages, suggesting that CD163 lacks involvement with ASFV infection. This work provides a framework for VV as an early infection surrogate model in Vero cells, and helps close the door on the CD163 controversy.
Keywords: African swine fever; CD163; vaccinia virus; virus cell entry